Acute Variceal Bleeding - García-Pagán, Juan Carlos; Reverter, Enric; Abraldes, Juan G.; Bosch, Jaime (Seminars in Respiratory and Critical Care Medicine, 2012)
Bleeding from gastroesophageal varices is a frequent complication of cirrhosis. Mortality from a variceal bleeding episode has decreased in the last 2 decades from 40% to 15 to 20% due to the implementation of effective treatments and improvement in the general medical care. Initial treatment should include adequate fluid resuscitation and transfusion to maintain hemoglobin around 7 to 8 g/dL, and prophylactic antibiotics (norfloxacin or ceftriaxone). It is currently recommended that a vasoactive drug be started as soon as variceal bleeding is suspected. Vasoactive therapy should be maintained for up to 5 days to prevent early rebleeding. Where available, terlipressin, a vasopressin derivative, is the preferred agent because of its safety profile; it represents the only drug with proven efficacy in improving survival. Somatostatin and octreotide are used and are as effective as terlipressin in control of bleeding but have not been shown to reduce mortality. Endoscopic therapy must be performed within the first 12 hours after admission when the patient is stable. Variceal band ligation is the recommended endoscopic treatment, but injection sclerotherapy is an alternative if band ligation is technically difficult. Despite this standard of care, 10 to 20% of patients may still exhibit initial failure to control bleeding or early rebleeding within the first 5 days. In failures to control bleeding the use of rescue transjugular intrahepatic portosystemic shunt (TIPS) using covered stents is the best alternative. In mild early rebleeding a second course of endoscopic therapy may be attempted. If rebleeding is severe, placement of TIPS using covered stents is the first-choice rescue treatment. In refractory variceal bleeding episodes, balloon tamponade may be used as a temporary bridge to TIPS. Identification of patients that are at high risk of treatment failure may guide new strategies to improve outcomes. Indeed, a recent trial has shown that placement of TIPS, using covered stents, within 72 hours of admission in patients at high risk of treatment failure (i.e., those Child B with active bleeding or Child C less than 14 points) markedly decreased rebleeding and improved survival.
Keywords: cirrhosis; portal hypertension; variceal bleeding; endoscopic band ligation; sclerotherapy; terlipressin; somatostatin; tips